Non-invasive Estimation of Atrial Fibrillation Driver Position With Convolutional Neural Networks and Body Surface Potentials - Cámara-Vázquez, Miguel Ángel; Hernández-Romero, Ismael; Morgado-Reyes, Eduardo; Guillem, Maria S.; Climent, Andreu M.; Barquero-Pérez, Oscar (Frontiers in Physiology, 2021)
Atrial fibrillation (AF) is characterized by complex and irregular propagation patterns, and AF onset locations and drivers responsible for its perpetuation are the main targets for ablation procedures. ECG imaging (ECGI) has been demonstrated as a promising tool to identify AF drivers and guide ablation procedures, being able to reconstruct the electrophysiological activity on the heart surface by using a non-invasive recording of body surface potentials (BSP). However, the inverse problem of ECGI is ill-posed, and it requires accurate mathematical modeling of both atria and torso, mainly from computerized tomography (CT) or magnetic resonance (MR) images. Several Deep Learning-based methods have been proposed to detect AF, but most of the AF-based studies do not include the estimation of ablation targets. In this work, we propose to model the location of AF drivers from body surface potentials (BSP) as a supervised classification problem using Convolutional Neural Networks (CNN). Accuracy in the test set ranged between 0.75 (SNR=5dB) and 0.93 (SNR=20dB upwards) when assuming time independence, but it worsened to 0.52 or lower when dividing AF models into blocks. Therefore, CNN could be a robust method that could help to non-invasively identify target regions for ablation in AF by using body surface potential mapping, avoiding the use of ECGI.